Capability enhancement in compact digital holographic microscopy - Qu, Weijuan (2018)
A compact reflection digital holographic microscopy (DHM) system integrated with the light source and optical interferometer is developed for 3D topographic characterization and real-time dynamic inspection for Microelectromechanical systems (MEMS). Capability enhancement methods in lateral resolution, axial resolving range and large field of view for the compact DHM system are presented. To enhance the lateral resolution, the numerical aperture of a reflection DHM system is analyzed and optimum designed. To enhance the axial resolving range, dual wavelengths are used to extend the measuring range. To enable the large field of view, stitching of the measurement results is developed in the user-friendly software. Results from surfaces structures on silicon wafer, micro-optics on fused silica and dynamic inspection of MEMS structures demonstrate applications of this compact reflection digital holographic microscope for technical inspection in material science.